Size response of an SMPS-APS system to commercial multi-walled carbon nanotubes - Lee, Seung-Bok; Lee, Jun-Hyun; Bae, Gwi-Nam (SPRINGER, 2010)
Carbon nanotubes (CNTs) are representative-engineered nanomaterials with unique properties. The safe production of CNTs urgently requires reliable tools to assess inhalation exposure. In this study, on-line aerosol instruments were employed to detect the release of multi-walled CNTs (MWCNTs) in workplace environments. The size responses of aerosol instruments consisting of both a scanning mobility particle sizer (SMPS) and an aerodynamic particle sizer (APS) were examined using five types of commercial MWCNTs. A MWCNT solution and powder were aerosolized using atomizing and shaking methods, respectively. Regardless of the phase and purity, the aerosolized MWCNTs showed consistent size distributions with both SMPS and APS. The SMPS and APS measurements revealed a dominant broad peak at approximately 200-400 nm and a distinct narrow peak at approximately 2 mu m, respectively. Comparing with field application of the two aerosol instruments, the APS response could be a fingerprint of the MWCNTs in a real workplace environment. A modification of the atomizing method is recommended for the long-term inhalation toxicity studies.
Keywords: SURFACE-AREA; INHALATION TOXICITY; NANOPARTICLE; EXPOSURE; MASS; CLASSIFICATION; PARTICLES; SAFE